The Effect of Modified Audit Opinion on Borrowing Cash Flow and Investment Cash Flow on Non-Financial Companies - Praptitorini, Mirna Dyah; Kartika, Andi; Bhandari, Rahul; Ratsameemonthon, Chadchom; Nasir, Wan Mohd Nazdrol bin Wan Mohd; Supriyadi, Supriyadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
This study aims to test and analyze the effect of modified audit opinion on borrowing cash flow and investment cash flow. Factors that affect borrowing cash flow and investment cash flow are modified audit opinions. The control variables used are profitability, leverage, company size, and operating cash flow. The population and research sample are all non-financial companies listed on listed in the Indonesia Stock Exchange (IDX), National Stock Exchange of India Ltd (NSE), and the Stock Exchange of Thailand (SET) in 2016-2018. This study examined 930 data derived from non-financial companies listed on the Stock Exchange in the period 2016-2018. The analysis method used in this study used multiple regression analysis. The results of this study show that modified audit opinion has a significant negative effect on borrowing cash flow and investment cash flow. The variables of profitability control, company size, and operating cash flow have a significant positive effect on borrowing cash flow while leverage does not affect borrowing cash flow. The results of this study can be a recommendation for regulators or banks to make audit opinions one of the criteria for banks when lending and for company leaders to pay attention to matters related to the results of financial statement audits so that it can make it easier to obtain funding from outside the company.